2005
DOI: 10.1111/j.1467-842x.2005.tb00758.x
|View full text |Cite
|
Sign up to set email alerts
|

The short‐term effects of air pollution on daily mortality in four Australian cities

Abstract: Objective: To examine the short‐term health effects of air pollution on daily mortality in four Australian cities (Brisbane, Melbourne, Perth and Sydney), where more than 50% of Australians reside. Methods: The study used a similar protocol to APHEA2 (Air Pollution and Health: A European Approach) study and derived single‐city and pooled estimates. Results: The results derived from the different approaches for the 1996‐99 period showed consistent results for different statistical models used. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 17 publications
3
53
1
Order By: Relevance
“…For instance, a 10 mg/m 3 increase in previous day's PM 10 has been associated with a 0.27% and 0.35% increase in all-cause mortality (Dominici et al, 2005;Zeka et al, 2005); we found this increase to be 1.21% with PM 2.5 . A recent study of PM 2.5 and mortality in four Australian cities reported an almost identical effect size (Simpson et al, 2005) to ours. In our study, the largest specific-cause association with PM 2.5 occurred for respiratory related deaths and its magnitude was larger than that associated with PM 10 (Zeka et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…For instance, a 10 mg/m 3 increase in previous day's PM 10 has been associated with a 0.27% and 0.35% increase in all-cause mortality (Dominici et al, 2005;Zeka et al, 2005); we found this increase to be 1.21% with PM 2.5 . A recent study of PM 2.5 and mortality in four Australian cities reported an almost identical effect size (Simpson et al, 2005) to ours. In our study, the largest specific-cause association with PM 2.5 occurred for respiratory related deaths and its magnitude was larger than that associated with PM 10 (Zeka et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…163 Mortality associations with PM were also observed for nine French cities 164 and three Australian cities. 165 Two Asian multicity studies have reported daily mortality associations with measures of PM (see Table 1). The first was a study of seven major Korean cities.…”
Section: Multicity Studies Of Short-term Exposure Andmentioning
confidence: 99%
“…Reference % increase in mortality Global Review (Atkinson et al, 2014) 1.04 (0.52-1.56) USA (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986) (Klemm, 2003) (Levy et al, 2012) 1.2 (0.5-1.9) California (1999-2002) (Ostro et al, 2006) 0.6 (0.2-1.0) Spain (2003)(2004)(2005)(2006)(2007)) (Ostro et al, 2011) 1.4 (0.6-2.3) Australia (1996-1999) (Simpson et al, 2005) 0.9 (-0.7-2.5) Beijing (2007Beijing ( -2008) (Chen et al, 2011) 0.53 (0.37-0.69) Guangzhou (2007-2008) (Yang et al, 2012) …”
Section: Place (Study Year)mentioning
confidence: 99%